THE AMBIGUITY OF TIMOR-LESTE'S RELATIONSHIP WITH ASEAN: EXPLORING EXCLUSIONARY PRACTICES AND MEMBERSHIP PROCESS CHALLENGES - Soares, Fridolino Gama; Guterres, Alexandre De Sousa (International Journal of Science and Society, 2024)
The presence of Timor-Leste as an independent country but not fully integrated into ASEAN creates a complex relationship ambiguity. This article explores exclusionary practices that hinder Timor-Leste's membership process in ASEAN and the challenges faced in overcoming this ambiguity. Through an analysis of regional political dynamics, the article discusses how ASEAN manages the geopolitical complexities in Southeast Asia following Timor-Leste's independence in 2002. A descriptive analytical approach is used to understand the factors influencing the ASEAN membership process for Timor-Leste. The research highlights the role of ASEAN diplomacy in managing relations with Timor-Leste inclusively, in accordance with principles of sovereignty and regional security. The study concludes that Timor-Leste's membership process in ASEAN faces significant challenges, requiring a long-term strategy evaluation to integrate Timor-Leste effectively. Recommendations include deepening broader regional cooperation, strengthening ASEAN diplomacy, and building more open dialogue with Timor-Leste. These steps are expected to pave the way for resolving relationship ambiguities and enhancing regional stability in Southeast Asia. The parameters used in this research are Institutional Theory supported by a Historical-Comparative Approach.